Malocclusions in the koala (Phascolarctos cinereus). Issue 11 (21st October 2019) - Pettett, LM; Wilson, GJ; Nicolson, V; Boardman, WSJ; Speight, N; Fabijan, J; Trott, DJ; Bird, PS
Abstract : Malocclusions are a misalignment or incorrect positioning of the teeth when the upper and lower jaws close. These are poorly described in the koala and can result in irregular mastication which can have lifelong effects on body condition and oral health. A total of 370 koalas from two populations in Queensland (295) and one in South Australia (75) were examined for malocclusions. The prevalence of malocclusions in South Australian free‐ranging koalas, captive Queensland koalas and Queensland free‐ranging koalas was 39% (44), 30% (29) and 22% (29) respectively. Four types of malocclusion were identified based on severity of misalignment of the incisor/canine region, types 1, 2, 3 and 4. Maxillary overbite measurements of the molariform teeth were determined and these anisognathic values were then used to describe malocclusions within familial relationships in captive colonies. Captive koalas with a malocclusion had narrower mandibular width that ranged between 0.5 and 1% less than the normal measurements. The specific malocclusions reported in this study affected individuals by leading to tooth rotation, mobility and erosion with inefficient mastication of food and vegetation compaction. These changes increased the oral cavity pathology, by placing animals at risk of periodontal disease. There was evidence of familial links to malocclusion types in captive animals. Therefore captive breeding recommendations should consider known koala malocclusion traits to minimise their effect on future generations.